2014
DOI: 10.1016/j.envres.2014.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Mobilisation of lipophilic pollutants from blubber in northern elephant seal pups (Mirounga angustirostris) during the post-weaning fast

Abstract: Northern elephant seals (NES) (Mirounga angustirostris) from the Año Nuevo State Reserve (CA, USA) were longitudinally sampled during the post-weaning fast in order to study the mobilisation and redistribution of various classes of persistent organic pollutants (POPs), such as polybrominated diphenyl ethers (PBDEs), polychlorinated biphenyls (PCBs), dichlorodiphenyldichloroethylene (p,p'-DDE) and hexachlorobenzene (HCB) between blubber and blood. Inner and outer blubber layers were analysed separately. Organoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 50 publications
7
33
2
Order By: Relevance
“…Since TGs are composed of by FAs, and TGs are the main lipid fraction of adipose tissue, the present results may be compared to the total lipid percentages of blubber. Similar trends in the inner blubber layer of weaned NES pups were observed for the total lipid percentages, which were determined by gravimetry (Louis et al, 2014). This means that TG content remains stable in blubber throughout the fast, which may be surprising because TGs are heavily mobilised.…”
Section: Fatty Acidssupporting
confidence: 64%
See 4 more Smart Citations
“…Since TGs are composed of by FAs, and TGs are the main lipid fraction of adipose tissue, the present results may be compared to the total lipid percentages of blubber. Similar trends in the inner blubber layer of weaned NES pups were observed for the total lipid percentages, which were determined by gravimetry (Louis et al, 2014). This means that TG content remains stable in blubber throughout the fast, which may be surprising because TGs are heavily mobilised.…”
Section: Fatty Acidssupporting
confidence: 64%
“…This means that TG content remains stable in blubber throughout the fast, which may be surprising because TGs are heavily mobilised. Indeed, the lipid mass of weaned NES pups is reduced by 24-49% (Noren et al, 2003) and a net increase of free FA concentration between early and late fast is noted in their serum (our study and Louis et al (2014)). Moreover, a morphometric study of the weaned NES pup blubber was conducted earlier and showed that the proportions of small adipocytes increased in both blubber layers, whereas the proportions of large adipocytes decreased over the fast, reflecting a reduction of lipid content in the adipocytes (Louis et al, 2014).…”
Section: Fatty Acidssupporting
confidence: 50%
See 3 more Smart Citations